TRANSFORMASI DIGITAL PRAKTIK KONSELING PESANTREN MELALUI PLATFORM RUANG VIRTUAL BERBASIS PARTICIPATORY ACTION RESEARCH - Pamuji, Agus; Rindanah, Rina; Fadilah, M. Reyhan (LPPM Universitas Nusa Mandiri, 2026)
The rapid advancement of digital technology requires religious educational institutions to adapt to changes in service delivery, including counseling practices. In Islamic boarding schools (pesantren), counseling activities are still predominantly conducted through conventional approaches and have not fully utilized the potential of digital media. Based on this condition, this community service program aims to promote the digital transformation of counseling practices through the utilization of virtual platforms using the Participatory Action Research (PAR) approach. The program was implemented at Pondok Pesantren An-Nida, Cirebon City, through three main stages: observation, implementation, and participatory reflection. The observation stage was used to identify digital readiness and institutional needs, the implementation stage involved digital literacy training and virtual counseling simulations, and the reflection stage evaluated program effectiveness. The results indicate improved understanding, empathic communication skills, and awareness of digital ethics and privacy. The participatory approach proved effective in strengthening institutional collaboration and developing an adaptive cyber culture. This program demonstrates that digital transformation within Islamic boarding schools can harmoniously align with religious and ethical values when developed through collaborative, reflective, and sustainable processes.